GM-007 An economic analysis of the introduction of a ward based 'dispensing for discharge' pharmacy technician medicines management service. (25th February 2017) - Gunn, N; Thakrar, J; Reid, P
Abstract : Background: Most hospitals throughout the UK now use a 'dispensing for discharge' model for issuing medication to inpatients. There is significant evidence of substantial improvements in productivity and service delivery, but little evidence of financial savings currently exists. The data presented here aim to address the lack of financial evidence for this model. Purpose: To elucidate the drug cost benefit of introducing a pharmacy technician led 'dispensing for discharge' service. To prove that the service was cost beneficial after accounting for all associated staffing costs. Material and methods: Admission data derived from the hospital patient administration system were combined with pharmacy drug expenditure data. The data were then analysed to establish the drugs costs for all admissions to the two acute respiratory wards which had implemented the 'dispensing for discharge' service, versus two acute respiratory wards not running the ward based technician service. Data were reviewed for a period of 6 months from April 2015 to September 2015. Results: The results showed that the two 'dispensing for discharge' intervention wards had lower drug expenditure compared with the same months from the previous financial year: ward 1 had spent £9045 less and ward 2 had spent £12 743 less, for a combined total of £21 788 less. The non-intervention wards had higher drug expenditure compared with the same months from the previous financial year: ward 3 had spent £7972 more and ward 4 had spent £ 2225 more, for a combined total of £10 196 more. This resulted in a cumulative saving of £31 984 for the 6 months studied. This would equate to an estimated total year saving of £63 968. This was sufficient to offset all staffing costs associated with implementing the service and resulted in a small financial gain. This analysis does not take into account the wider financial impact, or quality improvements gained from increased patient service provision, safety and efficiency delivered by the ward based service. Conclusion: This analysis shows that the drug cost savings associated with the ward based technician service was sufficient to fully fund all associated staffing and setup costs, resulting in significant patient service improvements with no financial burden to the organisation. No conflict of interest